Cardiac manifestations of multisystem inflammatory syndrome - Izabela Nowakowska; Aleksandra Osiejewska; Anna Grądzik; Karolina Mikut; Małgorzata Kudan; Dominika Wojtachnio; Jakub Bartoszewicz; Anna Gorajek (Kazimierz Wielki University, 2022)
Introduction and purpose: Multisystem inflammatory syndrome (MIS) in children and adolescents is an excessive inflammatory response syndrome after storage of COVID-19, which can lead to serious complications. The course of the disease may vary from mild to requiring intensive therapy. In our review, we try to draw attention to the importance of cardiological complications and present the currently used treatment. In medical professionals vigilant should be increased in order to early recognize this disease, and to be alert to the need for early cardiological evaluation and follow-up. Description of the state of knowledge: MIS can cause myocardial dysfunction, shock, coronary artery lesions, pericardial effusion, valvulitis, and electrophysiological abnormalities. Patients may require intensive medical care, careful fluid therapy, the use of pressor amines and, in rare cases, extra corporeal membranę oxygenation (ECMO). Coronary aneurysms are the most important long-term complication of MIS. They occur in up to 25% of patients. Most abnormalities are retreated within 2-3 months. MIS has a good prognosis with a mortality rate of 2%. Summary: Cardiac complications, although serious, rarely require urgent intervention. Patients with diagnosed dilatation of the coronary arteries or aneurysm require intensive medical review in the initial period of recovery. The control must include a medical examination, ECG, ECHO and evaluation of markers of myocardial damage. Patients who have undergone MIS should be released from physical education for at least 6 weeks or until the changes in the coronary arteries disappear. The lesions resolve spontaneously in 2-3 months in most patients and do not recur, suggesting the possibility of waiving long-term patient follow-up.